P0900EXPLORE THE MECHANISM OF BEAUVERICIN ON THE OSTEOBLAST CELLS. (6th June 2020) - Lu, Chien-Lin; Lu, Kuo-Cheng
Abstract: Background and Aims: In chronic kidney disease (CKD), dysregulation in mineral and bone metabolism cause abnormal bone turnover disease. Over the past years, we focus the dysregulation of osteoblast and osteoclast in CKD. Numerous evidences have shown beauvericin (BEA), a cyclic hexadepsipeptide from Codyceps cicadae, possesses anti-convulsion, anti-arrhythmia, sedation, and anti-tumor activities. The mechanism of the BEA cytotoxicity on osteoblast remains fully unclear. During bone formation and fracture healing, osteoblasts and chondrocytes undergo an orderly developmental progression that ultimately ends in apoptosis. It is still unclear what signal transduction pathways are used of beauvericin in programmed cell death in osteoblasts and its effect on bone turnover. Method: 7F2 cell line is cultured in Dulbecco's modified eagle medium (DMEM). To induce osteoblast differentiation, a total of 1 × 10 5 7F2 cells were plated in a 6-cm dish containing 100 μg/mL ascorbic acid, and 10 mM β-glycerol phosphate in the absence or presence of a 0-3μM dose of Beauvericin overnight. The cytotoxic effect of BEA was first determined using the MTT method. Cell lysates were prepared by extracting proteins with lysis buffer, and western blots were developed with a peroxidase-conjugated secondary antibody, and then proteins were visualized by enhanced chemiluminescence (ECL) procedures. Results: To clarify the rational of inhibitory effect of beauvericin on osteoblast, preosteoblast 7F2 cells were treated with 0-3μM beauvericin overnight. The extent of cell viability after 5-day culture period and observed through microscopy and MTT assay. Figure 1 showed Beauvericin can significantly decrease the number of differentiated osteoblasts in a dose dependent manner. Figure 2 in MTT assay showed the 7F2 osteoblast cells survival rate was significant reduced under beauvericin treatment, especially in high dose of beauvercin. Western blot analysis in Figure 3 showed that under 2 μM Beauvericin dose treatment, the expression of Bax protein was increased and conversely the expression of BCl-2 was decreased. Conclusion: Taken together, we thought Beauvercin induce 7F2 osteoblast cells death and might be in a relation to apoptosis. However, the further detail mechanism is need further investigated.